2013
DOI: 10.1097/ta.0b013e3182a92514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resuscitation fluids on endothelial glycocalyx, venular blood flow, and coagulation function after hemorrhagic shock in rats

Abstract: Our findings support the concept of cardiovascular and microvascular stabilization by infused FFP, in which the increase in microvascular perfusion associated with restored EG is essential for an optimal resuscitation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
107
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 34 publications
13
107
2
3
Order By: Relevance
“…Using electron microscopy images of venules, Kozar et al (32) reported similar data in a more severe model of hemorrhagic shock. Different studies suggested at least partial recovery of the damaged glycocalyx by treatment with plasma and other blood-derived resuscitation fluids, but not by treatment with crystalloids (32,59,60). These data suggested that fluid resuscitation could prompt further changes in the glycocalyx after an initial hemorrhage-induced degradation.…”
mentioning
confidence: 98%
“…Using electron microscopy images of venules, Kozar et al (32) reported similar data in a more severe model of hemorrhagic shock. Different studies suggested at least partial recovery of the damaged glycocalyx by treatment with plasma and other blood-derived resuscitation fluids, but not by treatment with crystalloids (32,59,60). These data suggested that fluid resuscitation could prompt further changes in the glycocalyx after an initial hemorrhage-induced degradation.…”
mentioning
confidence: 98%
“…[18,19] However, a sudden influx of liquid into the blood vessels will cause the infused blood to be retained in the venous system as the blood is in a state of stasis in the capillaries, which will cause a constant increase in the intravascular hydrostatic pressure. [13,[20][21][22] In turn, this results in more intravascular liquid penetrating into the extravascular space through the blood vessel walls, which already show increased permeability due to the ischemic and hypoxic injury. Consequently, this process can cause edema of the internal organs, especially pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of plasma volume with crystalloid and/or synthetic colloid solutions produces a diffuse microvascular bleeding tendency due to dilution of clotting factors, accelerated endothelial glycocalyx degradation and direct interactions with fibrin polymerization (178,183,204). The induction of acidosis to a pH of less than 7.2 via intravenous administration of hydrochloric acid or ischemia-reperfusion injury has been shown to reduce the enzymatic activity of coagulation proteases, producing a coagulopathy that cannot be readily reversed with simple correction of the acidosis (192)(193)(194).…”
Section: Discussionmentioning
confidence: 99%
“…However only 3 models have evaluated aspects of the proposed pathophysiologic mechanisms, and as a result animal models are yet to significantly contribute to the improved mechanistic understanding of ATC (40,177,178).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation